The Christie affair - Gramont, Nina de (New York : St. Martin's Press, 2022)
"London, 1925: In a world of townhomes and tennis matches, socialites and shooting parties, Miss Nan O'Dea became Archie Christie's mistress, luring him away from his devoted and well-known wife, Agatha Christie. The question is, why? Why destroy another woman's marriage, why hatch a plot years in the making, and why murder? How was Nan O'Dea so intricately tied to those eleven mysterious days that Agatha Christie went missing?"--
Includes bibliographical references (pages 310-311).
Keywords: Christie, Agatha, -- 1890-1976 -- Fiction; Missing persons -- Fiction; Mistresses -- Fiction; Adultery -- Fiction; Murder -- Fiction; Great Britain -- History -- George V, 1910-1936 -- Fiction; Historical fiction; Biographical fiction